Differences among sulfated proteoglycans synthesized in nonchondrogenic cells, presumptive chondroblasts, and chondroblasts. - Okayama, M (1976)
The sulfated proteoglycans synthesized by definitive chondroblasts in cultured 10-day chick vertebral or epiphyseal cartilages were characterized by their sedimentation profile in a sucrose gradient and their susceptibility to chondroitinase ABC (EC 4.2.2.4; chondroitin ABC lyase). These sulfated proteoglycans were indistinguishable from those synthesized by definitive chondroblasts that emerge from older cultures of somites plus notochord or in older cultures of limb buds. The sulfated proteoglycans of these definitive chondroblasts are readily distinguished from those synthesized by their mother cells, the presumptive chondroblasts, or those synthesized by dedifferentiated or bromodeoxyuridine-suppressed chondroblasts. However, the sulfated proteoglycans synthesized by presumptive chondroblasts or by dedifferentiated or bromodeoxyuridine-suppressed chondroblasts cannot be dintinguished by these techniques from those synthesized by (i) blastodisc cells, (ii) fibroblasts, (iii) spinal cord cells, or (iv) skeletal, cardiac, or smooth muscle cells. Addition of glycosaminoglycans or collagen to the medium did not induce somite or limb presumptive chondroblasts to synthesize the chondroblast-unique sulfated proteoglycans. Cells moving from the presumptive chondroblast compartment into the chondroblast compartment acquire not only the option to initiate the synthesis of chondroblast-unique collagen chains, but also the capacity to synthesize chondroblast-unique sulfated proteoglycans.